PAAR‐Rhs proteins harbor various C‐terminal toxins to diversify the antibacterial pathways of type VI secretion systems. (18th January 2017) - Ma, Jiale; Sun, Min; Dong, Wenyang; Pan, Zihao; Lu, Chengping; Yao, Huochun
Summary: The type VI secretion system (T6SS) of bacteria plays a key role in competing for specific niches by the contact‐dependent killing of competitors. Recently, Rhs proteins with polymorphic C‐terminal toxin‐domains that inhibit or kill neighboring cells were identified. In this report, we identified a novel Rhs with an MPTase4 (Metallopeptidase‐4) domain (designated as Rhs‐CT1) that showed an antibacterial effect via T6SS in Escherichia coli . We managed to develop a specific strategy by matching the diagnostic domain‐architecture of Rhs‐CT1 (Rhs with an N‐terminal PAAR‐motif and a C‐terminal toxin domain) for effector retrieval and discovered a series of Rhs‐CTs in E. coli . Indeed, the screened Rhs‐CT3 with a REase‐3 (Restriction endonuclease‐3) domain also mediated interbacterial antagonism. Further analysis revealed that vgrGO1 and eagR/DUF1795 (upstream of rhs‐ct ) were required for the delivery of Rhs‐CTs, suggesting eagR as a potential T6SS chaperone. In addition to chaperoned Rhs‐CTs, neighborless Rhs‐CTs could be classified into a distinct family (Rhs‐Nb) sharing close evolutionary relationship with T6SS2‐Rhs (encoded in the T6SS2 cluster of E. coli ). Notably, the Rhs‐Nb‐CT5 was confirmed bioinformatically and experimentally to mediate interbacterial antagonism via Hcp2B‐VgrG2 module. In a further retrieval analysis, we discovered various toxin/immunity pairs in extensive bacterial species that could be systematically classified into eight referential clans, suggesting that Rhs‐CTs greatly diversify the antibacterial pathways of T6SS.